Functional Characterization of BoaMYB51s as Central Regulators of Indole Glucosinolate Biosynthesis in Brassica oleracea var. alboglabra Bailey - Cai, Congxi; Yuan, Wenxin; Miao, Huiying; Deng, Mingdan; Wang, Mengyu; Lin, Jiayao; Zeng, Wei; Wang, Qiaomei (Frontiers in Plant Science, 2018)
R2R3-MYB transcription factor MYB51 is known to control indole glucosinolate (indole GSL) biosynthesis in Arabidopsis. Here, two copies of BoaMYB51 have been isolated in Chinese kale (Brassica oleracea var. alboglabra Bailey), designated BoaMYB51.1 and BoaMYB51.2, which exhibit overlapping but distinct expression levels among different organs and respond to upstream signaling molecules in a similar pattern. It has been demonstrated a structural and functional conservation between BoaMYB51s and AtMYB51 by phylogenetic analysis, complementation studies and transient expression assay. To further investigate the transcriptional mechanism, we identified the transcriptional activation domain (TAD) and putative interacting proteins of BoaMYB51s by means of yeast (Saccharomyces cerevisiae) two hybrid. Using tobacco (Nicotiana benthamiana) transient expression assay, we confirmed that the carboxy-end is required for transcriptional activation activity of BoaMYB51s. In addition, several BoaMYB51-interacting proteins have been identified by yeast two-hybrid screening. These results provide important insights into the molecular mechanisms by which MYB51 transcriptionally regulates indole GSL biosynthesis.